2013
DOI: 10.1603/an12127
|View full text |Cite
|
Sign up to set email alerts
|

Sense Organs on the Antennal Flagellum of Leptoglossus zonatus (Heteroptera: Coreidae)

Abstract: For the first time, antennal sensorial organs of Leptoglossus zonatus (Dallas) (Heteroptera: Coreidae) are described through scanning electron microscopy. The antennae are formed by a scape, pedicel, and a flagellum that is composed of two flagellomeres and is the main bearer of sensorial organs. Five types of sensory structures were identified: Trichoid sensilla, basiconic sensilla, coeloconic sensilla, campaniform sensilla, and placoid sensilla. Trichoid sensilla were divided into five subtypes. The large st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 31 publications
5
29
0
Order By: Relevance
“…Their position, shape and structure evidently suggest a mechanosensitive function in the studied taxa. The same shape and size of sensilla campaniformia were described in some taxa of heteropterans such as Reduviidae: Triatominae (Catalá 1997 ), Coreidae (Gonzaga-Segura et al 2013 ), in four species of pentatomids (Ahmad et al 2016 ) and currently on the antenna of gerromorphan species. It seems that these sensilla are common in most taxa of Heteroptera.…”
Section: Morphology and Mechanoreception Of Sensillamentioning
confidence: 52%
See 3 more Smart Citations
“…Their position, shape and structure evidently suggest a mechanosensitive function in the studied taxa. The same shape and size of sensilla campaniformia were described in some taxa of heteropterans such as Reduviidae: Triatominae (Catalá 1997 ), Coreidae (Gonzaga-Segura et al 2013 ), in four species of pentatomids (Ahmad et al 2016 ) and currently on the antenna of gerromorphan species. It seems that these sensilla are common in most taxa of Heteroptera.…”
Section: Morphology and Mechanoreception Of Sensillamentioning
confidence: 52%
“…However, in Hydrometridae, sensilla trichoidea can also respond to touch. Similarly, the shape and function of the antennal sensilla chaetica in some heteropterans was described by Catalá ( 1997 ), Chinta et al ( 1997 ), da Rosa et al ( 1999 ), Silva et al ( 2010 ), Rani and Madhavendra ( 1995 , 2005 ) and Gonzaga-Segura et al ( 2013 ), who indicated that they have a mechanosensitive role, which enables true bugs to determine the position of their antenna with respect to their surroundings. Similarly, Keil ( 1997 ) mentioned that sensilla chaetica may allow detection and transmission of diverse mechanical stimuli.…”
Section: Morphology and Mechanoreception Of Sensillamentioning
confidence: 61%
See 2 more Smart Citations
“…Sensilla coeloconica (SCO) were found only on the second segment of the flagellum of A. chinensis. Sensilla with similar morphological features were found on the flagellum of N. viridula, C. purpurea (West), E. heros, P. guildinii and L. zonatus (Brézot et al 1997, Rani & Madhavendra 2005, Silva et al 2010, Gonzaga-Segura et al 2013 and Reduviidae (Catalá 1997). In social insects, such as ants and wasps, whose behavior is guided by variations in temperature, sensilla coeloconica are chemoreceptors that respond to air temperature changes (Ruchty et al 2009).…”
Section: Discussionmentioning
confidence: 82%